ANALISIS KEPEMIMPINAN TRANSFORMASIONAL DI PT. MEGA ANDALAN KALASAN, YOGYAKARTA - , Niken Dwiyandari ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Leaders are those who can give effect to subordinates, peers and superiors because they fullly have an understanding of the vision and mission of the organization to achieve common goals for the organization's success to goes well. To become a leader takes a long process that is influenced by education, working experience, knowledge and talent possessed. One thing for sure as a requirement of a great leader they must have main character and talent nature to influence people surrounding their environment. The vision and mission of the organization is steering purposes shall be understood by all unit members. Without the referral they will have different perceptions and goals to a leader or group unit. To achieve that goal the leader is needed, to invite by directing members to have the same behavior as the unit works, influence and motivate all members of the organization to give big contribution to the success of the organization's goals, that is what we call the identity of the organization. In 1985, Bass, develop a concept model of leadership consisting of transformational leadership (4 dimensions) and transactional leadership (3- dimensional), seven dimensions were stated in an instrument called multifactor Leadership Questionnaire (MLQ), which is a scale that identifies the characteristics of leaders and support individuals find the perception that suit to the type of their leaders. Bass in his research concluded that transformational leadership can improve the commitment and performance of its members so that members will be totally involved in contributing and loyal to superiors. Transformational leadership, consisting of four dimensions, which are: Idealized Influence, when the leader becomes a role model that is admired, respected and trusted. Leaders instill confidence in its members so that the team members will be able to do the job without a hitch and the resulting sense of pride in their leaders. Inspirational Motivation, when leaders provide inspirational motivation to work and make the unit strong and solid in achieving organizational goals. Intellectual Stimulation, a leader have intellectual stimulation through a rational approach, find problems solving encountered with the different aspects. Individualized Consideration, when leaders give attention and treat individuals according to their individual needs.